EFEKTIVITAS KERJASAMA INTERNASIONAL PONDOK PESANTREN UNTUK PENINGKATAN MUTU SUMBER DAYA MANUSIA: PONDOK MODERN GONTOR DALAM KERJASAMA INTERNASIONAL - Novi Rizka Amalia (Lembaga Penelitian Universitas Trisakti, 2019)
Indonesia is one of the countries with the most Muslim population in Asia. But this does not change the idiotic foundation of Indonesia, namely Pancasila, which is the basis of how the nation and state are also useful for determining the Direction of Foreign Policy of the Republic of Indonesia. As social beings, humans cannot live alone in state relations, one country certainly needs a role and cooperation with other countries. Every collaboration will certainly have a positive impact. One of the positive results underlined in this study is about the development of HR (Human Resources) which can be done through various things. This study will discuss the benefits of international cooperation in improving the quality of human resources carried out by Islamic Boarding Schools, given the number of Islamic boarding schools in Indonesia. The benefits are imitated in terms of both language and non-academic abilities, the benefits will be useful for the installation process at the Islamic Boarding School.